(untitled) (Journal of Hama University, 2020)
This study was conducted to determine the effect of supplementing salvia officinals leaves powder on some productive traits and carcass characteristics.. 165 broiler chicks of Ross 308 one day old were used. Birds have been assigned to 5 treatments with 3 replicated each treatment contain 33 chicks. The first treatment is control (G1), the second treatment is the second group G2, Neomycin supplementation was added by 200 mg / kg feed, the third fourth and fifth treatments were supplemented of salvia officinalis leaves powder at 0.5%, 0.75%, and 1% it was named S1,S2 and S3. Results showed that adding salvia officinalis leaves powder to broiler mixtures at all concentrations led to improve productive traits as body weight (BW) and feed conversion(p≤0.05) comparing with control group(G1). Results showed adding salvia officinalis leaves powder to rations led to improve of carcass characteristics acting increase of weight of main pieces (thight ,leg , big breast , small breast ) and increase weight of wings and neck .